A Study on the Trade of Arabs and Its Impact During the Ancient Period: Exploring the economic and geographic significance of Arab trade during ancient times (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Arabia which stands at the cross roads of threecontinents, Asia, Europe and Africa, has the distinction of being the centre ofthe old world. Its shores are washed by the Mediterranean Sea, the Red Sea, theIndian Ocean, the Gulf of Oman, and the Persian Gulf. Where the seas end, thehistoric rivers, the Euphrates and the Tigris form the boundary between Iraqand Arabia.